An innovative 3-D nanoforest heterostructure made of polypyrrole coated silicon nanotrees for new high performance hybrid micro-supercapacitors. Issue 26 (14th July 2015) - Aradilla, David; Gaboriau, Dorian; Bidan, Gérard; Gentile, Pascal; Boniface, Maxime; Dubal, Deepak; Gómez-Romero, Pedro; Wimberg, Jan; Schubert, Thomas J. S.; Sadki, Saïd
<x xml:space="preserve">Abstract</x> A micro-supercapacitor electrode made of polypyrrole coated silicon nanotrees.